Lack of plastid‐encoded Ycf10, a homolog of the nuclear‐encoded DLDG1 and the cyanobacterial PxcA, enhances the induction of non‐photochemical quenching in tobacco. (14th December 2021) - Trinh, Mai Duy Luu; Hashimoto, Akira; Kono, Masaru; Takaichi, Shinichi; Nakahira, Yoichi; Masuda, Shinji
Abstract: pH homeostasis in the chloroplast is crucial for the control of photosynthesis and other metabolic processes in plants. Recently, nuclear‐encoded Day‐Length‐dependent Delayed Greening1 (DLDG1) and Fluctuating‐Light Acclimation Protein1 (FLAP1) that are required for the light‐inducible optimization of plastidial pH in Arabidopsis thaliana were identified. DLDG1 and FLAP1 homologs are specifically conserved in oxygenic phototrophs, and a DLDG1 homolog, Ycf10, is encoded in the chloroplast genome in plant cells. However, the function of Ycf10 and its physiological significance are unknown. To address this, we constructed ycf10 tobacco Nicotiana tabacum mutants and characterized their phenotypes. The ycf10 tobacco mutants grown under continuous‐light conditions showed a pale‐green phenotype only in developing leaves, and it was suppressed in short‐day conditions. The ycf10 mutants also induced excessive non‐photochemical quenching (NPQ) compared with those in the wild‐type at the induction stage of photosynthesis. These phenotypes resemble those of Arabidopsis dldg1 mutants, suggesting that they have similar functions. However, there are distinct differences between the two mutant phenotypes: The highly induced NPQ in tobacco ycf10 and the Arabidopsis dldg1 mutants are diminished and enhanced, respectively, with increasing duration of the fluctuating actinic‐light illumination. Ycf10 and DLDG1 were previously shown to localize in chloroplast envelope‐membranes, suggesting that Ycf10 and DLDG1 differentially control H + exchange across these membranes in a light‐dependent manner to control photosynthesis.